The Role of Da'wah In Kuala Nerang And Its Implications - Ahmad Tarmizi B. Ismail (Universiti Sains Islam Malaysia, 2022)
This academic research discusses the role of da'wah which played by the authorities around Kuala Nerang and its implications to the societies. There are many institutions and individuals involved in spreading Islamic belief (da 'wah) in this town. This is because the members of societies are not pay a serious attention towards Islamic values in their heart. The scope of this research focused on Kuala Nerang town only and it's considered as one of field research type. The methodology in this research is applied by using the method of interviewing, documentation and observation. The result of the research shows that the government institutions and private sectors are definitely playing the important roles in spreading the teaching of Islam among the societies. Many methods, ways and strategies were taken by the authorities in order to enhancing Islamic teaching and its values into societies. Finally the research gives this society an opportunity to understand Islamic teachings and practice it properly in their life.